Teacher’s Effort To Improve The Learning Understanding Of Slow Learner - Zhani, Vira Ulfia; Lubis, Yani (Jurnal Ragam Pengabdian, 2026)
Slow learners often experience difficulties in understanding and retaining learning materials, requiring instructional strategies that accommodate their cognitive characteristics. This study aims to investigate teachers’ efforts to improve slow learners’ learning comprehension through the implementation of the Feynman Technique and Active Recall in inclusive classrooms. A qualitative case study design was employed involving classroom teachers and slow learners selected through purposive sampling. Data were collected through in-depth interviews, classroom observations, and documentation, and analyzed using the Miles and Huberman interactive model. The findings revealed that teachers integrated the Feynman Technique by encouraging students to explain concepts in their own words and implemented Active Recall through repeated questioning, retrieval exercises, and gradual reinforcement of learning materials. The combination of these strategies enhanced students’ classroom participation, conceptual understanding, and memory retention compared to conventional explanation-based instruction. The study also found that the effectiveness of both strategies was strengthened when supported by individualized guidance, visual learning media, and emotional support. The novelty of this study lies in the integration of the Feynman Technique and Active Recall as complementary cognitive-based strategies to improve both comprehension and retention among slow learners in inclusive classroom settings.